Virtual Reality-Based Approach to Evaluate Emotional Everyday Scenarios for a Digital Health Application - Valentin Wunsch; Effi Freya Picka; Hanna Schumm; Joshua Kopp; Tamer Abdulbaki Alshirbaji; Herag Arabian; Knut Möller; Verena Wagner-Hartl (Multimodal Technologies and Interaction)
Social interactions are a part of our everyday lives. This can be challenging for individuals who experience social interactions as demanding, such as persons with autism spectrum disorder (ASD). Therefore, different types of training exist to help individuals affected by ASD practice in challenging situations. Digital applications offer advantages over traditional training because they can better address the individual needs of people with ASD. The development of a therapeutic application initially requires identifying appropriate emotion-relevant scenarios of social interaction. Based on a previous study evaluating text-based scenarios with different levels of complexity, a virtual reality (VR) environment was developed to assess the applicability of the scenarios in VR. Therefore, an experimental study was conducted. Two different scenarios of social interaction, each with four different levels of complexity, were presented and evaluated by 18 participants (10 males, eight females). A multidimensional approach was used to combine subjective assessments and psychophysiological measures (ECG and EDA). The results showed that the implementation of the scenarios in VR was able to differentiate between different levels of complexity. As the long-term target is to implement the findings in a therapeutic application for people with ASD, the results of the study are promising for the achievement of this goal.